Nanodelivery systems of thymoquinone for improving its bioavailability and efficiency in the food and biomedical applications - Shaddel R; Rashidinejad A; Karimkhani MM; Tarhan O; Jafari SM (Elsevier B V, 2025)
Thymoquinone (TQ), a hydrophobic bioactive constituent of Nigella sativa seeds, has garnered attention for its potential in treating various ailments due to its antioxidative and anti-inflammatory properties. However, TQ's hydrophobicity, instability in varying pH environments, photosensitivity, rapid hepatic metabolism, and low bioavailability present major challenges for its application in pharmaceutical and nutraceutical formulations. Nanotechnology offers innovative nanocarriers that can overcome these limitations. Notable among these are lipid-based nanocarriers (e.g., nano-liposomes, nano-emulsions, niosomes, solid lipid nanoparticles, and nanostructured lipid carriers), biopolymeric systems (e.g., nano-hydrogels, nanofibers, nanotubes, and cyclodextrin inclusion complexes), and inorganic nanocarriers. These delivery systems are designed to enhance TQ's solubility, protect it from degradation, and improve its bioavailability and therapeutic performance. Despite numerous advances, the clinical and industrial translation of these nano-delivery systems remains limited, primarily due to scalability issues, regulatory constraints, and a lack of standardized evaluation protocols for food and biomedical use. This review provides a comprehensive analysis of these nanocarriers, emphasizing their mechanisms for TQ encapsulation, controlled release, and bioaccessibility enhancement. It also highlights current limitations and outlines future directions for their development. Unlike previous reviews, this work offers a comparative evaluation of nanocarrier systems for both food and biomedical applications, addressing their effectiveness, limitations, and readiness for real-world translation. The key takeaway is that among the various approaches, lipid-based and biopolymeric nanocarriers have demonstrated the greatest potential for enhancing TQ delivery, particularly in oral and functional food formulations, as well as targeted cancer therapy, due to their biocompatibility, scalability, and effective release profiles.
Keywords: Nanocarriers; Bioavailability; Nano-liposomes; Nano-emulsions; Biopolymeric nanostructures